Takwin Al-Bi’ah Al-Lugoh Al-Arabiyah fi Ma’had ‘Abdurrahman bin ‘Auf bi Malang - SALMAS, AHMAD NURUL HUDA (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
The study aims to describe the formation of an Arabic language environment in Ma’had Abdurrahman bin A’uf Malang. This school is one of Islamic boarding schools in Malang known for its Arabic language environment and as an education institution of Arabic language and Islamic study, which applied direct method in Arabic learning. Ma’had Abdurrahman bin A’uf Malang used the curriculum of I’dad Lughowi at Ibnu Su’ud University in Saudi and the teachers at Ma’had Abdurrahman bin A’uf Malang were required to graduate from the Universities of the Middle East. This study conducted using a qualitative research with a case study method. In collecting the data, this study organized the observation, interview and documentation. The result shows that the formation of the Arabic language environment in Mahad Abdurrahman bin A'uf is due to the use of direct methods in learning both inside and outside the classroom, so as to create an Arabic language environment that could improve the competence of students. One of the facilities provided by Mahad Abdurrahman bin 'Auf to support good Arabic learning is by providing boarding schools for students. In the dormitory, the students can directly practice what they have learned in the classroom. In the formation of the Arabic language environment, there are several obstacles faced by such as students who are not disciplined in Arabic. As for the solution made by Ma'had, namely by imposing stricter rules on the students so that the formation of the environment is well formed.